Do Higher Wages Reflect Higher Productivity? Education, Gender and Experience Premiums in a Matched Plant-Worker Data Set - Torbjørn Hægeland; Tor Jakob Klette (Statistics Norway, Research Department, 1997)
Do wage differences between workers with high and low levels of education, between males and females and between workers with different levels of experience reflect differences in productivity? We address this set of questions on the basis of a data set with variables for individual workers matched with a comprehensive data set for manufacturing plants in Norway for the period 1986-93. The results suggest that workers with higher education tend to be more productive, roughly in accordance to their wage premium. Female workers are cet. par. found to be less productive than male workers, and this is reflected in their wages. Experienced workers are on average found to be more productive. For workers with 8 to 15 years of experience, the productivity premium exceeds the wage premium, while the opposite is the case for workers with more than 15 years of experience.
Keywords: J24; J31; 330; Education; Gender; Experience; Wage differences; productivity; Plant level data; individual worker data